2018
DOI: 10.1139/tcsme-2018-0055
|View full text |Cite
|
Sign up to set email alerts
|

Vibration stability analysis of dual motor harmonic synchronous excitation nonlinear vibration conveyer

Abstract: To enhance the stability of a harmonic vibration synchronous conveyer, this paper establishes a nonlinear dynamical model for this kind of vibration machine, and the effects and compensation function on the stability produced by the nonlinearity of a master vibration spring have been analyzed. A small parameter perturbation method has been used to analyze the effects of a nonlinear force on the conveyer when a fluctuating impact was loaded onto the machine. The reaction between motion stability of the vibratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…According to the design of the fast terminal sliding mode surface shown in (11), the full expression of FTSMC can be stated as follows:…”
Section: Ftsmc Algorithm For Controlling the Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the design of the fast terminal sliding mode surface shown in (11), the full expression of FTSMC can be stated as follows:…”
Section: Ftsmc Algorithm For Controlling the Systemmentioning
confidence: 99%
“…A permanent magnet in-wheel motor (PMIWM) can be seated in the small space of the wheel of HEVs [8,9]. The performance of PMIWMs is sensitive to uncertain external factors such as temperature, vibration, magnetic saturation [10][11][12][13] and affects the comfort and safety of a vehicle. Therefore, the research on the control system of PMIWMs should take the external factors into consideration.…”
Section: Introductionmentioning
confidence: 99%
“…The vibrating systems driven by two eccentric rotors are widely used in the industrial field, such as: vibrating screen, vibratory feeder, shakeout machine, vibration conveyor, etc. The vital factor, affecting the stability of the vibrating system, is the synchronous characteristics of two eccentric rotors, so the researches about the synchronization of eccentric rotors became a hot topic in the scientific research field in recent years [1][2][3][4][5][6][7][8][9][10][11]. In the meanwhile, vibration synchronization is the most common synchronization method, and is favored by the majority of scholars.…”
Section: Introductionmentioning
confidence: 99%
“…Further, Fang et al discussed the synchronization characteristics of two rotors vibration system, and revealed that the synchronization performance are affected by the system's parameters, coupling coefficients, and rotation direction of rotor [4,5,7]. Li et al investigated the reaction between motion stability of the vibration conveyer and the synchronization of the two motors [6]. Zhang et al studied the synchronization and stability of two unbalanced rotors separately driven by induction motors [9].…”
Section: Introductionmentioning
confidence: 99%